Rancang Bangun Sistem Informasi Akuntansi Di Stiki Copy Center - Haris, Lucky Hardiyanti Kartika; Ardiana, Dewa Putu Yudhi; Udayana, I Putu Agus Eka Darma (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
Abstract STIKI Copy Center is one place of business that provides print, copy, scan and sells office stationery services. Financial reporting process that occurs in STIKI Copy Center is still not in accordance with the financial statements should be and still use Ms.Excel which makes the owner feel difficulty in the process of calculating the current formula. The financial statements made at Ms.Excel can be manipulated by someone or the owner can do inputting with the same data so that it can cause redundancy and can also cause incompatibility of data and data that could be lost or deleted if infected by a virus or accidentally deleted. This research aims to design and build an accounting information system at STIKI Copy Center which begins with the stages of identifying problems, conducting data collection, analyzing system modeling using UML, building systems using the laravel framework and MySQL database. The results of this research are financial applications based website that will process the transaction income and expenses and print reports general ledger, balance sheet, income statement, statement of changes in capital and is also equipped with a revenue graph for each month. From the test results by using black box testing can be seen that the system has been going well as expected